Video for Change: Creating and Measuring Ethical Impact. (7th August 2017) - Notley, Tanya; Gregory, Sam; Lowenthal, Andrew
Abstract: 'Video for Change' refers to the practice of using video as a means to activate progressive social change. Ongoing work in this field seeks to define and establish ethical considerations that can inform and direct Video for Change as an emerging practice. This article reports on a research project carried out with a network of Video for Change organizations. The purpose of this project was to inform the development of an impact framework that could be used to support Video for Change practitioners to design for—and evaluate—their social impact in a way that is considered ethically appropriate. The project began by investigating what makes Video for Change a unique media practice and by considering its genealogy. This was followed by an examination of the ethics and ethical practices that are most valued by Video for Change practitioners. This article reports on research key findings, and proposes an Impact Pathways framework, while also highlighting key challenges associated with designing—and assessing—the social impact of video initiatives across diverse contexts.